Peran Pemerintah Desa dalam Meningkatkan Kesejahteraan Masyarakat: Studi Kasus di Desa Tumbang Olong II - Yorgen Kaharap; Ida Bagus Suryanatha (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Tumbang Olong II Village is a village that still faces various challenges in improving the welfare of its community. Therefore, this research is important to be conducted to identify the role of village governments in overcoming these challenges and supporting the improvement of the welfare of village communities. The theory of village community welfare includes a variety of approaches used to understand and improve the welfare of villagers. The research method used in this study is a qualitative case study. The qualitative approach was chosen because it allows researchers to understand more deeply the role of village governments in improving community welfare. The people of Tumbang Olong II Village have a harmonious social life with a high spirit of mutual cooperation. This village has several tourist attractions that can attract tourists, such as Bun-Bun waterfall tourism and white sand tourism. The existence of this natural tourism can be used as the main attraction to develop the village tourism sector. The role of the village government is very important in improving the welfare of the community. Through functions such as regulation, community empowerment, and resource management, village governments can have a significant positive impact.